A General Model of Inter-State Relations: the Contemporary Reality and a Way-Out. - Singh, Satya Prakash (2008)
The aim of this paper is to capture the contemporary reality of inter-state relations in India. Toward that it develops a general classification of actions of states. These are defined on the basis of anticipated end and/ or realized consequences for the participating states. It is a two-state model, though the conclusions can be generalized for multi-state situations. Each state is assumed to take into account not only self-interest but also the interest of others in its decision making process. The usual model of behavior of two parties, each maximizing or sacrificing self-interest, so dear to social scientists, more so to economists, is a special case of the model outlined here. In the process, the contemporary reality of inter-state relationships is captured. It is seen that the Indian system, as it is emerging is drifting away from the desired path of unity and cooperation, except in case of emergencies and natural calamities. As much of the inter-state conflicts arise due to the attitude and mindset of the decision makers, it is argued that if people learn to organize their lives around the fourfold frame of our ancient human values the conflicts shall reduce and cooperation, harmony and coordination amongst the states shall improve